(untitled) (Research, Society and Development, 2020)
The Malvaceae family is constituted of herbaceous, shrub and tree plants, found in all phytogeographic domains in Brazil, with species for food, ornamental and landscape use. The study aimed to contribute to the expansion of knowledge and geographical distribution of three species of Malvaceae to Maranhão. The collection of botanical material was carried out in a fragment of vegetation, located in the urban area of the municipality of Caxias / MA, between the months of February 2017 and March 2018. The samples were herborized according to the usual techniques in plant taxonomy and species identification was carried out through specialized bibliography. The species of Melochia parvifolia Kunth, Sida ciliaris L. and Sida urens L. occur in Maranhão, with wide distribution in Brazil and in all types of vegetation. Based on the results, the taxa distribution area is expanded to Maranhão and Northeast Brazil. Descriptions, identification key, images and distribution map are presented for the registered Malvaceae species.